The motorway achievement. Volume 1, - Baldwin, Peter, 1922-2010; Baldwin, Robert (Thomas Telford, 2004)
This volume provides a set of contrasting first hand accounts of the creation of the motorway system, the problems encountered the solutions adopted and the lessons learned for future motorway development.
Keywords: Express highways -- Great Britain -- History.; elektronické knihy; electronic books